2015
DOI: 10.1080/13102818.2015.1068135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bacteria-free filtrate fromBacillus megateriumstrain L2 on the mycelium growth and spore germination ofAlternaria alternata

Abstract: Strain L2 (a Bacillus megaterium species that was isolated from tobacco's rhizosphere) was applied to inhibit the pathogen Alternaria alternata in an attempt to reduce tobacco brown spot disease. This study focused on inhibition experiments, in which culture filtrate inhibited A. alternata's mycelium growth, its spore germination rate and its spore output. The results indicated that an approximately 1.5%À20% concentration of the bacteria-free filtrate, could effectively inhibit hyphae growth. Additionally, bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 17 publications
6
30
0
Order By: Relevance
“…Conversely, a recent study by Li et al . () reported that CF from Bacillus megaterium strain L2 at concentrations of 1·5–20% could effectively inhibit the conidial germination of Alternaria alternata . This is in contrast to the present results, in which lower concentrations inhibited the conidia of fungal pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a recent study by Li et al . () reported that CF from Bacillus megaterium strain L2 at concentrations of 1·5–20% could effectively inhibit the conidial germination of Alternaria alternata . This is in contrast to the present results, in which lower concentrations inhibited the conidia of fungal pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation that exposure to Cf Ter331 induces in A . niger an abnormal hyphal branching pattern (Fritsche et al ., ; Kai et al ., ) as well as the expression of genes involved in cell membrane repair (Mela et al ., ) is in line with a mode of action that involves membrane damage in fungi (Lin and Momany, ; Li et al ., ). This is consistent with the physical damage to plasma cell membranes and increased membrane permeability that have been proposed as modes of action for other polyyne‐like compounds (Garrod et al ., ; Lee et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Bacterially produced inhibitors of fungal spore germination can shape the outcome of interactions between fungi and plants, animals or humans, and thus may have practical relevance for managing fungi that are pathogenic to such hosts (Fisher et al ., ). Mechanisms behind the observed bacterially induced arrest of fungal spore germination are not always known (Li et al ., ; Nogueira et al ., ) but include the bacterial synthesis of compounds with antagonistic activity, such as organic acids (Le Lay et al ., ) and cyclic lipopeptides (Chitarra et al ., ; Gong et al ., ), or metabolites that confer a competitive advantage, such as siderophores (Kousser et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations